Design, development and testing of a wearable hybrid energy harvester for sustainable gadgets - Alsaad, Abdulla; Ahmad, Iftikhar; Aawan, Adel; Abdelrhman, Ahmed M.; Khan, Wajid (Advanced Sensor and Energy Materials, 2025)
This research paper presents the design, development and testing of a novel wearable hybrid energy harvester (WH-EH) aimed at powering sustainable gadgets. By harnessing energy using both electromagnetic and piezoelectric transduction mechanisms to capture ambient mechanical energy from human body motion, this device offers a versatile solution to the growing demand for portable and renewable energy. The paper details the integration of both mechanisms into a single device that fits in human shoes and the practical implications of deploying such technology in everyday gadgets. The WH-EH comprised of 3D printed frame, a cantilever beam made up of stainless steel, two permanent neodymium magnets residing at the tip of the cantilever beam, two printed circuit board-based micro planar coils that were fixed to the top and bottom of the 3D printed frame. Through rigorous testing, the WH-EH has demonstrated significant potential of producing maximum a power of 577 μW which can help in reducing the reliance on traditional power sources and advancing the frontier of wearable technology. Energy harvesters like WH-EH are pivotal in advancing the sustainability of wearable gadgets, diminishing the dependence on traditional battery sources. These innovations not only strengthen the longevity and eco-friendliness of personal electronics but also align with global sustainable development goals, particularly in the energy and environmental sectors. The progression of such energy harvesters marks a crucial milestone in the ongoing integration of renewable energy practices into daily electrical applications.